The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1128/mcb.00337-06
|View full text |Cite
|
Sign up to set email alerts
|

BMAL1 Shuttling Controls Transactivation and Degradation of the CLOCK/BMAL1 Heterodimer

Abstract: CLOCK and BMAL1 are bHLH-PAS-containing transcription factors that bind to E-box elements and are indispensable for expression of core circadian clock components such as the Per and Cry genes. A key step in expression is the heterodimerization of CLOCK and BMAL1 and their accumulation in the nucleus with an approximately 24-h periodicity. We show here that nucleocytoplasmic shuttling of BMAL1 is essential for transactivation and for degradation of the CLOCK/BMAL1 heterodimer. Using serial deletions and point m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
162
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(191 citation statements)
references
References 52 publications
28
162
0
1
Order By: Relevance
“…In this study, we demonstrate that CCA1 and LHY have similar expression patterns, bind to a similar region of the Lhcb1*3 promoter, colocalize in the nucleus, and that they can physically interact both in vitro and in plants. These findings are consistent with the evidence showing the involvement of dimerization between core oscillator components in the mammalian system (Kwon et al, 2006) and in Drosophila (Meyer et al, 2006), suggesting that homodimerization and heterodimerization might be conserved aspects in the regulation of eukaryotic circadian clocks.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we demonstrate that CCA1 and LHY have similar expression patterns, bind to a similar region of the Lhcb1*3 promoter, colocalize in the nucleus, and that they can physically interact both in vitro and in plants. These findings are consistent with the evidence showing the involvement of dimerization between core oscillator components in the mammalian system (Kwon et al, 2006) and in Drosophila (Meyer et al, 2006), suggesting that homodimerization and heterodimerization might be conserved aspects in the regulation of eukaryotic circadian clocks.…”
Section: Discussionsupporting
confidence: 91%
“…Next, we tested the role of the adrenal peripheral clock in producing the daily CS rhythm in vivo by ablating the molecular clockwork specifically in the adrenal CS-producing cells. We chose BMAL1 as a target for knockdown because our previous studies show that it plays the determining role in posttranslational regulation and function of the CLOCK:BMAL1 heterodimer (24,25) and, more importantly, CLOCK has an overlapping role with NPAS2, another member of core clock components (26). We generated a transgenic (TG) mouse line in which a part of the BMAL1 coding region was expressed in an antisense orientation under tissue-specific control by using the 1.3-kb ACTH receptor (MC2R) promoter (MC2R-AS-BMAL1; see Figs.…”
Section: Circadian Rhythms Of Cs Production and Adrenal Steroidogenicmentioning
confidence: 99%
“…The mechanism of PER/CRYdependent repression is complex and is not yet well understood. It has been shown that CRYs regulate posttranslational modifications, nuclear/cytoplasmic distribution and stability of CLOCK and BMAL1 proteins as well as the interaction of the CLOCK/BMAL1 complex with chromatin modifying enzymes [19][20][21]. All these activities are likely to contribute to CRYdependent inhibition of CLOCK/BMAL1 functional activity.…”
Section: Circadian Clock Organizationmentioning
confidence: 99%